2016
DOI: 10.1186/s13229-016-0090-z
|View full text |Cite|
|
Sign up to set email alerts
|

22q11.2 duplication syndrome: elevated rate of autism spectrum disorder and need for medical screening

Abstract: BackgroundWidespread use of microarray technology has led to increasing identification of 22q11.2 duplication syndrome (22q11.2DupS), the reciprocal syndrome of the well-characterized 22q11.2 deletion syndrome (22q11.2DS). Individuals with 22q11.2DS have elevated rates of community diagnoses of autism spectrum disorder (ASD), schizophrenia, and a range of medical problems and birth defects that necessitate extensive medical screening. Case reports of 22q11.2DupS include patients with ASD, fewer medical problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
80
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 12 publications
(16 reference statements)
18
80
2
3
Order By: Relevance
“…Thus, we calculated the incidence of ASD in symptomatic individuals in our study together with those reported in the literature and from the DECIPHER database to observe a prevalence rate of 31% (8/26; see Table ), including two DECIPHER patients (#249936 and #276067). Our finding is in agreement with estimated rates of 14%–25% for ASD diagnosis in symptomatic individuals with a typical duplication (Wenger et al., ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Thus, we calculated the incidence of ASD in symptomatic individuals in our study together with those reported in the literature and from the DECIPHER database to observe a prevalence rate of 31% (8/26; see Table ), including two DECIPHER patients (#249936 and #276067). Our finding is in agreement with estimated rates of 14%–25% for ASD diagnosis in symptomatic individuals with a typical duplication (Wenger et al., ).…”
Section: Resultssupporting
confidence: 93%
“…We found that nested duplications in this study were not associated with congenital heart disease, although there are two such cases reported in DECIPHER (#280410 and #278381). Despite this, nested duplications remain less frequently associated with congenital heart defects when compared to typical A‐D duplications (8% atypical nested vs. 24% typical) (Wenger et al., ); however, we acknowledge that our results are based on a small sample size. Nevertheless, this observation suggests that nested atypical duplications could present with reduced penetrance for significant clinical phenotypes such as cardiac defects, hypotonia, and hearing impairment when compared to the larger typical duplications.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Frequently, both gain and loss variations are found and associated with severe phenotypes including neurological conditions such as seizures, intellectual disability, and cerebral malformations. 22q11.2 microdeletion/duplication syndrome is strongly associated with neurological and psychiatric disorders such as autism, bipolar disorder, schizophrenia, intellectual disability, and epilepsy [Kao et al, 2004;Robin et al, 2006;Lemke et al, 2009;Karayiorgou et al, 2010;Stoll et al, 2013;Kim et al, 2016;Strehlow et al, 2016;Wenger et al, 2016]. The TOP3B gene encodes a topoisomerase DNA (III) β protein.…”
Section: Resultsmentioning
confidence: 99%